ANALISIS KOMPENSASI TERHADAP TURNOVER INTENTION KARYAWAN - Teratai, Nona Ratu Syifa Putri; Hanum, Nazwa; Fitriyani, Desy (Bussman Journal : Indonesian Journal of Business and Management, 2024)
The phenomenon of high turnover in Indonesia has become a particular concern for companies, especially in retaining competent human resources. Employee turnover is often triggered by percieved inadequate compensation, both financial and non-financial. This article aims to analyze the relationship between compensation and employee turnover intention and identify strategies that can be implemented to reduce turnover rates. This study employs a literature approach to collect secondary data from various studies and credible sources. The analysis results indicate that fair and competitive compensation significantly reduce employees’ intentions top leave the company